Micellization and Related Behaviours of Polyoxyethylene-Type Non-ionic Surfactants on Root Elongation of Allium cepa L. - Yilmaz, Gulden; Akbas, Halide; Dane, Feruzan; Leventer, Sinem; Ozturk, Fatmanur (Asian Journal of Chemistry, 2012)
In this study, polyoxyethylenated fatty alcohol ether (POE) nonionic surfactants polyoxyethylene (23) lauryl ether (C12E23) (Brij 35); polyoxyethylene (10) cetyl ether (C16E10) (Brij 56); polyoxyethylene (10) stearyl ether (C18E10) (Brij 76); polyoxyethylene (10) lauryl ether (C12E10) (POE 10). A large proportion nonionic surfactants are made hydrophilic by the presence of a polyethylene glycol chain obtained by the polycondensation of ethylene oxide. They are called polyethoxylated nonionics. In this study the effects of polyoxyethylene-type nonionic surfactants on root elongation of Allium cepa L. were determined for a week under laboratory conditions in the concentration ranges of 5.00, 2.50 and 1.25 g/L (w/v) at 16 ± 0.5 ºC. It was determined that the stimulatory effect on root elongation becomes stronger when the number of ethylene oxide group (C2H4O) was increased in the POE surfactant. The stimulatory effect decreases in the order C18E10 > C16E10 > C12E23 > C12E10 due to the decreasing of the number hydrocarbons in the series.